Osteoblast Viability of Liquid Smoke Rice Hull and Nanoparticles Form as Periodontitis Treatment - Arundina, Ira; Diyatri, Indeswati; Juliastuti, Wisnu S.; Budhy, Theresia I.; Surboyo, Meircurius D. C.; Iskandar, Benni; Ramaniasari, Sheryn M.; Moelyanto, Azzahra S. A.; Saputra, Gustiadi (European Journal of Dentistry, 2022)
Objective Rice husk liquid smoke nanoparticles have the potential to be developed as a drug because they have anti-inflammatory effects that can modulate the process of osteoblast stimulation through osteoblast stimulation by thorough small size and enter cells easily. The osteoblast is the key of alveolar regeneration in periodontitis treatment. This present study analyzed the differences of liquid smoke rice husk and nanoparticles of liquid smoke rice husk on osteoblast viability as periodontitis treatmentMaterials and Methods The liquid smoke rice husk was obtained from the pyrolysis process. The nanoparticles were made with chitosan, maltodextrin, and difference of concentration of liquid smoke rice husk (such as 1, 2.5, 5, 7.5, 10, 12.5, 15, and 17.5%). The viability of osteoblast was analyzed by 2,5-diphenyl-2H-tetrazolium bromide (MTT) assay.Statistical Analysis The data were analyzed using independent t-test to analyze the differences between liquid smoke rice husk and nanoparticles of liquid smoke rice husk, the significant was set a p<0.05.Result The nanoparticles of liquid smoke rice husk showed higher osteoblast viability compared liquid smoke rice husk. The nanoparticles' concentration of 5, 7.5, and 10% showed higher osteoblast viability compared liquid smoke rice husk (p = 0.002, 0.000, and 0.001, respectively).Conclusion The nanoparticles of liquid smoke rice husk showed higher viability of osteoblast. This confirmed that the nanoparticles were able to reduce the toxicity in the higher concentration of liquid smoke of rice husk.
Keywords: nanoparticles; liquid smoke; rice husk; osteoblast and human and health